(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
Defining the boundaries of practice is an important prerequisite for the developing of professional responsibility and a crucial condition of raising awareness and understanding of professional tasks and responsibility of specialists in social pedagogy. Through time in different countries the professional boundaries of social pedagogy have been constantly changing. That’s why the concept of social pedagogy is different from country to country. In Ukraine we have an issue of defining clear and understandable boundaries of socio-pedagogical theory and practice. Thus, the aim of given article was to analyze origins and main tendencies of social pedagogy and close practices (social work and pedagogy) in European countries to establish basic parameters. To understand the difference between three social practices, there have been defined basic distinguishing criteria: the idea; the main prerequisite; specific research tasks; specific practical tasks and general characteristic of technologies. The main idea of pedagogy is cognition, while social work practice comes from an idea of integration and social change. And, ultimately, the main idea of social pedagogy is inclusion and empowerment to promote individuals’ social functioning, participation, social belonging and social competence. The specific scopes of its responsibility are: problems of inclusion in social processes and life managing. The prerequisite of classical pedagogy is relatively stable social system and established social values / standards. The basic precondition of social work are social problems resulted from violation of human rights, social injustice or difficult/extreme circumstances. And essential for appearance and developing of socio-pedagogical ideas was social injustice as a result of social inequality. Therefore, the main tasks of those social practices are differed as well. Pedagogy have to design the best possible conditions for the cognition and thinking processes development. Social work has to elaborate and improve new social conditions of life and human well-being, while the main task of social pedagogy is designing an individuals’, groups’ and communities’ life perspective.